2020
DOI: 10.32598/irj.18.3.969.1
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Dynamic Neuromuscular Stabilization Breathing Exercises on Chest Mobility, Trunk Muscles, and Thoracic Kyphosis: A Randomized Controlled 6-Week Trial

Abstract: Objectives: Dynamic Neuromuscular Stabilization (DNS) approach evaluates and activates the spinal stabilizers to optimize the performance of posture and respiratory system. This study investigated the effects of DNS breathing exercises on upper and lower chest wall mobility (UCM and LCM), trunk extensor endurance, and thoracic kyphosis in a group of sedentary students with poor posture. Methods: In this randomized, controlled 6-week trial, 52 participants were randomly divided into two groups: a DNS breathing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 19 publications
2
8
0
Order By: Relevance
“…After some practice time, patients can indirectly distinguish their position without knowing its anatomical location with awareness and correction (Frank et al, 2013;Kolář et al, 2009;Kolar & Kobesova, 2010;Milic ´, 2020). Movement of the rib cage is a crucial factor in airflow during both inspiration and expiration stem in mechanical characteristics of the rib cage and muscle tension (Milic ´, 2020;Mirtz, 2001;Mohammad Rahimi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After some practice time, patients can indirectly distinguish their position without knowing its anatomical location with awareness and correction (Frank et al, 2013;Kolář et al, 2009;Kolar & Kobesova, 2010;Milic ´, 2020). Movement of the rib cage is a crucial factor in airflow during both inspiration and expiration stem in mechanical characteristics of the rib cage and muscle tension (Milic ´, 2020;Mirtz, 2001;Mohammad Rahimi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…During the exercise, they paid particular attention to the stereotype of inhalation and exhalation. The participants were encouraged to expand the lower chest cavity and the whole abdominal wall proportionally during inhalation and maintain adequate equivalent tension of all abdominal wall sections during exhalation as described by the DNS manual (Canales et al, 2017;Davidek & Andel, 2018;Frank et al, 2013;Mahdieh et al, 2020;Mohammad Rahimi et al, 2020). Supervised exercises were performed on Saturday, Monday and Wednesday and home-based exercises were performed on Sunday, Tuesday, and Thursday.…”
Section: Dns Training Protocolmentioning
confidence: 99%
“…The chest expansion test was selected to test the mobility of the rib cage [ 12 , 13 ]. While in a seated position, the patient was asked to breathe in gradually through the nose, using lung expansion to push the measuring tape as much as possible, then to breathe out through the mouth as completely as possible.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, it is crucial to identify factors and measures that can improve the efficiency of the diaphragm. Numerous studies have shown a correlation between the activity of the diaphragm and intercostal muscles and respiratory and postural function [15][16][17]. Many experts argue that maintaining proper posture is essential for regular respiratory function [18].…”
Section: Introductionmentioning
confidence: 99%
“…To achieve success in any corrective or rehabilitation program that focuses on the movement system, it is important to consider retraining and correcting faulty respiratory patterns. Accordingly, to effectively perform breathing exercises, it is necessary to train in the corrective program under different conditions [9,16,17,19]. The dynamic neuromuscular stabilization (DNS) method, which is based on developmental kinesiology models, can achieve these goals [20,21].…”
Section: Introductionmentioning
confidence: 99%